TAWARAN STUDI AGAMA HINGGA FEMINISME BAGI ILMU HUBUNGAN INTERNASIONAL - M. Yustian Yusa; M. Yusuf Qardlawi (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2021)
This paper explored some methods and approaches in qualitative methodology in international relations research, from religious, literature, anthropology and feminism approaches. At the end, with the interdisciplinary approach that showed the prons and cons in international relations research—multi perspectives but the lost of identity epistemologically.